Diversity Problematics in Political Development Theories - Mawlood, Imad Ahmad (Journal of Legal and Political Studies, 2020)
The study of issues of diversity of societies is one of the most prominent problems facing contemporary political theories, and many theories have dealt with it, including the theory of multiculturalism and the theory of recognition. However, the study of diversity is not limited to these theories, as most of the statements and concepts that these theories dealt with have been examined in some form starting from the fifties of the 20th century by the pioneers of the theories of political development. However, the treatment of diversity issues within the framework of political development theories was a unilateral and negative treatment at the same time. This is due to the intellectual and political foundations upon which the theories of political development are based, so that these theories have taken the European model of government based on the state-nation and based on the rule of the majority as a basis for judging the backwardness of the societies of the third world countries and a political reference for overcoming this backwardness. So is the model of socialist rule based on working class rule. However, both models found in the diversity of the third world countries a source of political instability and a generator of political development crises as a crisis (legitimacy, participation, distribution, integration, penetration, etc.) as well as the crisis of economic and social backwardness.
Keywords: Diversity; Political Development; Multiculturalism; Instability; Political Development Crises